ANALISIS PERBANDINGAN ALGORITMA ASIMETRIS ELGAMAL DAN MASSEY-OMURA DALAM ENKRIPSI DAN DEKRIPSI DATA - Wijaya, Ahmad Adi; Wamiliana, Wamiliana; Andrian, Rico (Universitas Lampung, 2016)
Information can be kept secure by an encryption process in cryptograpy technigue. In this research we discussed comparative analysis of asymmetric algorithms ElGamal and Massey-Omura in terms of their complexities, time, and speed performances. The testing was conducted using 30 data with size varies between 66 bytes and 2000 bytes. Thirty data were tested 50 times. The result shows that Elgamal Algorithm is faster in encryption and decryption compared to Massey-Omura Algorithm and the complexity of both algorithms are linear algorithms (O (n)).